Complementary medicines and therapies in clinical guidelines on pregnancy care: A systematic review. Issue 4 (July 2022) - Ee, Carolyn; Levett, Kate; Smith, Caroline; Armour, Mike; Dahlen, Hannah G.; Chopra, Prakshi; Maroun, Paulette; Rao, Vibhuti S.; Avard, Nicole; Grant, Suzanne; Keedle, Hazel; Armour, Susanne; et al.
Abstract: Background: There is a need for evidence-based guidance on complementary medicines and therapies (CMT) use during pregnancy due to high prevalence of use and lack of guidance on the balance of benefit and harms. Aim: Evaluate the extent to which current clinical practice guidelines relevant to Australian healthcare professionals make clear and unambiguous recommendations about CMT use in pregnancy, and synthesise these recommendations. Methods: The search included EMBASE, PubMed, the National Health and Medical Research Council's Clinical Practice Guidelines Portal, and websites of Australian maternity hospitals and professional/not-for-profit organisations for published guidelines on pregnancy care. Data were synthesised narratively. Guidelines were appraised by two independent reviewers using the Appraisal of Guidelines for Research and Evaluation (AGREE II) instrument. Findings: A total of 48 guidelines were found, of which 41% provided recommendations that were not limited to routine vitamin and mineral supplementation. There were wide variations in recommendations, particularly for vitamin D and calcium. There was some consensus on recommending ginger and vitamin B6 for nausea and vomiting, and additional supplementation for women with obesity. Guidelines generally scored poorly in the domains of editorial independence and rigour of development. Discussion: There is a lack of guidance with regard to appropriate CMT use during pregnancy, which may result in less-than-optimal care. Inconsistency between guidelines may lead to variations in care. Conclusion: Guidelines should include clear and unambiguous guidance on appropriate CMT use during pregnancy, be based on a structured search of the evidence and informed by stakeholder engagement.